Thermal properties of polyurethanes and polyacrylates with trioxoimidazolidine rings - Zarzyka-Niemiec, I.; Lubczak, J. (Polimery, 2022)
New polyurethanes and polyacrylates containing imidazolidine rings were obtained from N,N’-bis(2-hydroxyalkyl)parabanates and Izocyn T-80 or acrylic and methacrylic acid, respectively. The polymers show usually higher thermal stability or heat resistance in comparison with their analogues obtained from aliphatic diols or classic polyacrylates.